Kinetic studies of Candida parapsilosis phagocytosis by macrophages and detection of intracellular survival mechanisms - Tóth, Renáta; Tóth, Adél; Papp, Csaba; Jankovics, Ferenc; Vágvölgyi, Csaba; Alonso, Maria F.; Bain, Judith M.; Erwig, Lars-Peter; Gácser, Attila (Frontiers in Microbiology, 2014)
Even though the number of Candida infections due to non-albicans species like C. parapsilosis has been increasing, little is known about their pathomechanisms. Certain aspects of C. parapsilosis and host interactions have already been investigated; however we lack information about the innate cellular responses towards this species. The aim of our project was to dissect and compare the phagocytosis of C. parapsilosis to C. albicans and to another Candida species C. glabrata by murine and human macrophages by live cell video microscopy. We broke down the phagocytic process into three stages: macrophage migration, engulfment of fungal cells and host cell killing after the uptake. Our results showed increased macrophage migration towards C. parapsilosis and we observed differences during the engulfment processes when comparing the three species. The engulfment time of C. parapsilosis was comparable to that of C. albicans regardless of the pseudohypha length and spatial orientation relative to phagocytes, while the rate of host cell killing and the overall uptake regarding C. parapsilosis showed similarities mainly with C. glabrata. Furthermore, we observed difference between human and murine phagocytes in the uptake of C. parapsilosis. UV-treatment of fungal cells had varied effects on phagocytosis dependent upon which Candida strain was used. Besides statistical analysis, live cell imaging videos showed that this species similarly to the other two also has the ability to survive in host cells via the following mechanisms: yeast replication, and pseudohypha growth inside of phagocytes, exocytosis of fungal cells and also abortion of host cell mitosis following the uptake. According to our knowledge this is the first study that provides a thorough examination of C. parapsilosis phagocytosis and reports intracellular survival mechanisms associated with this species.